Growth rates of shellfish blood (anadara granosa) At different stocking density - Ferta Praja; Rusliadi '; Mulyadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Information about stocking densities that are ideal for the cultivation of shellfish blood is still very limited. The aim of the study was to determine the stocking density in the rearing of blood clams. The benefits of this research was to provide information about the best stocking density for the growth of the blood clam and can be used as reference in the cultivation and further research. This study was conducted over 60 days from March to May 2013, in the village of Commander King, District Concong Affairs, Indragiri Hilir District, Riau Province. The method used was an experimental method with a completely randomized design (RAL) with three levels of the factor treatment. Treatment 1 (stocking density of 50 animals), treatment 2 (stocking density of 100 fish), Treatment 3 (stocking density of 150 fish) . Each treatment had 3 replication. Extensive research with size of each treatment area size was 50 x 50 cm (2500 cm2) fenced round with polyethylene net size of 0,5 inches. Seeds obtained from the blood clam catches directly in nature by local fishermen. Seeds stocked with as many as 900 tail with 2,33 cm and in length an average weight of 2,72 grams. The result showed that the growth length of the shellfish blood was 3,21 cm and the growth rates of 5,18 grams.Keywords: Shellfish blood, stocking density, seed, growth